Pengaruh Layanan Konseling kelompok dengan teknik self-management terhadap pengurangan kecanduan game online pada remaja - Kharisman, Rahman kharisman Rahman; Tawil, Tawil; Putro, Hijrah Eko (Borobudur Counseling Review, 2021)
The study aimed to test the influence of group counseling self-management techniques to reduce online gaming in adolescents. This research is a type of experimental quasi research with research design used is pre test – post test one group. The study subjects were selected by purposive sampling. The sample used as many as 8 adolescents as an experimental group. The data collection instrument used is the scale of online gaming addiction. The hypothesis test in this study uses parametric analysis, namely paired sample t-test with the help of SPSS 24.0 for windows program. The results showed that group counseling with self-management techniques was influential to reduce online gaming addiction behavior, this was evidenced by the results of the Paired sample t test of the experimental group with Sig probability. (2-tailed) 0.000< 0.05. Based on the analysis of an average decrease of 88.62 experimental groups that fall into the low category. Keywords: Group Counseling ; Self-Mangement Techniques ; Online Games